2016
DOI: 10.1053/j.gastro.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Mediates Evasion From Hepatitis C Virus Neutralizing Antibodies

Abstract: BACKGROUND & AIMS:Efforts to develop an effective vaccine against hepatitis C virus (HCV) have been hindered by the propensity of the virus to evade host immune responses. HCV particles in serum and in cell culture associate with lipoproteins, which contribute to viral entry. Lipoprotein association has also been proposed to mediate viral evasion of the humoral immune response, though the mechanisms are poorly defined. METHODS: We used small interfering RNAs to reduce levels of apolipoprotein E (apoE) in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 38 publications
2
54
0
5
Order By: Relevance
“…This quantitative difference in HCVpp and HCVcc neutralization may be explained by the recent demonstration by Fauvelle et al (2016) that ApoE increases HCVcc neutralization resistance.…”
Section: Agreement Between Hcvcc and Hcvpp Neutralizationmentioning
confidence: 99%
“…This quantitative difference in HCVpp and HCVcc neutralization may be explained by the recent demonstration by Fauvelle et al (2016) that ApoE increases HCVcc neutralization resistance.…”
Section: Agreement Between Hcvcc and Hcvpp Neutralizationmentioning
confidence: 99%
“…A recent study showed that binding of ApoE to HCV virions mediates viral evasion from neutralizing antibodies (51). Although the binding of HCV with ApoE intracellularly or extracellularly may have only a slight influence on the virus life cycle, the interaction of either pseudo-viral particles or…”
Section: Discussionmentioning
confidence: 99%
“…These include cell-to-cell transmission [150,284], interfering antibodies [279], apolipoprotein E [285], N-linked glycosylation [256,257,286], and a broad neutralization protection mechanism involving shielding by HVR1 [143,259,[287][288][289]. The latter research was spurred by the earlier finding that an HVR1 deleted genotype 1a recombinant was viable in vivo [290], an observation later expanded to different genotype recombinants in cell culture [288].…”
Section: Shielding Of Hcv From Neutralizationmentioning
confidence: 99%